Prevalence And Antibiotic Resistance Pattern of Extended Spectrum Beta-Lactamase (ESBL) Producing Escherichia Coli Isolated From Patients of Urinary Tract Infection in a tertiary care hospital, Dhaka. (East West Medical College Journal, 2026)
Background: Extended-spectrum β-lactamases producing Escherichia coli (ESBL-EC) lend resistance to most β-lactam antibiotics. Because of limited treatment options, ESBLEC infection generally more difficult to treat, leading to higher hospital costs, reduced rates of microbiological and clinical responses. This study aimed to determine the prevalence and antibiotic resistance pattern of ESBL-EC isolated from patients with urinary tract infection in a tertiary care hospital, Dhaka. Materials and methods: This retrospective laboratory-based cross-sectional study was conducted at East West Medical College and Hospital, Turag, Dhaka from January 2024 to December 2024. A total of 1902 urine samples were collected from urinary tract infection patients and processed by standard microbiological methods. According to the CLSI guidelines In vitro susceptibility testing to different antibiotics of all identified isolates of E. coli was performed following Kirby–Bauer’s disc diffusion method on Mueller–Hinton Agar. Results: Among 1902 urine samples 535 (28.12%) were culture positive. Among culture positive isolates around 369 (68.97%) Gram negative isolates and 166 (31.03%) Gram positive isolates were found. E. coli and Staphylococcus aureus were the most isolated organism among Gram-negative and Gram-positive isolates respectively. Out of 227 isolates 64 (28.19%) were ESBL producers, of which 40 (62.5%) isolated from adult patients (over the age of fifty), Most of the ESBL producers was isolated from indoor patients 36 (56.25%). Among ESBL-producing E. coli, the highest antibiotic resistance was observed with ceftazidime (100%), ampicillin (98.43%), cefepime (100%), ceftriaxone (100%), aztreonam (98.43%) and ciprofloxacin (78.12%) and the highest antibiotic sensitivity was observed with carbapenem (100%), fosfomycin (98.43%), nitrofurantoin (93.75%) and gentamicin (55.56%). Conclusion: The development of antibiotic resistance by ESBL-E. coli, the most frequent pathogen linked to urinary tract infections plays a crucial role in determining which antibiotic therapy is appropriate. This study highlights the importance of ongoing surveillance to guide empiric therapy and promote appropriate antibiotic use.EWMCJ Vol. 14, No. 2, July 2026: 170-178